Pharmacological inhibition of myostatin/TGF-β receptor/pSmad3 signaling rescues muscle regenerative responses in mouse model of type 1 diabetes - Jeong Jaemin; Conboy Michael J; Conboy Irina M (Acta Pharmacologica Sinica, 2016)
Aim: To study the influence of acute experimental diabetes on the regenerative potential of muscle stem (satellite) cells in mice. Methods: Male C57BL/6 young mice were injected with a single dose of streptozotocin (STZ, 180 mg/kg, ip) to induce diabetes. The diabetic mice were treated with insulin (0.75 U/kg, ip), follistatin (12 μg/kg, im) or Alk5 inhibitor (5 μmol/L per kg, sc) once a day. On the first day when high glucose levels were found, cardiotoxin (CTX) was focally injected into tibialis anterior and gastronemius muscles of the mice. The muscles were harvested 3 d and 5 d after CTX injection, and myofibers and satellite cells were isolated. Quantitative ex vivo and in vivo assays of myogenic potential were used to evaluate the muscle regenerative responses. Results: The satellite cells from the diabetic mice 3 d after CTX injection fail to activate, and the repair of muscle deteriorates, resembling that observed in old control mice. Furthermore, the satellite cells have excessive levels of myostatin, TGF-β receptor 1, pSmad3 and the cell cycle inhibitor p15, while the level of TGF-β1 remain unchanged. Treatment of the diabetic mice with insulin rescued muscle regenerative responses, and restored the expression levels of myostatin, TGF-β receptor 1, pSmad3, and p15 to those similar of healthy controls. Treatment of the diabetic mice with the myostatin antagonist follistatin, or with the Alk5 inhibitor of TGF-β receptor 1 (which did not diminish the blood glucose levels) rescued muscle regenerative responses and attenuated the myostatin/ TGFβ receptor/pSmad3 signaling. Conclusion: The muscle regenerative responses are incapacitated and repair of the tissue fails within hours after the initiation of hyperglycemia in a mouse model of type 1 diabetes, but stem cell function is rescued by insulin, as well as follistatin or an Alk5 inhibitor that blocks TGF-β receptor signaling.